1975
DOI: 10.1063/1.430842
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium constants of hydrogen–deuterium–tritium self-exchange reactions in water vapor as studied with a pulsed molecular-beam quadrupole mass filter

Abstract: We measured the equilibrium constants KHDO = P2HDO/PH2O⋅PD2O, KHTO = P2HTO/PH2O⋅PT2O, and KDTO = P2DTO/PD2O⋅PT2O at 295.6°K (22.4°C), assuming the mass spectrometric sensitivities of the three species cancel in each expression of the equilibrium constant. The results obtained were KHDO = 3.82±0.05, KHTO = 3.66±0.06, and KDTO = 3.99±0.07. These values agreed with the current theoretical values of KHDO = 3.84, KHTO = 3.69, and KDTO = 3.97 at the same temperature. We discuss the discrepancy of the present value o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

1977
1977
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 12 publications
1
13
0
1
Order By: Relevance
“…For the water vapor internal equilibrium reaction: H 2 O + D 2 O = 2HDO, large deviations were found between theoretical studies and experiments (Pyper et al, 1967;Pyper and Newbury, 1970;Pyper and Christensen, 1975). Wolfsberg (1969) showed that it was not sufficiently accurate to add anharmonic corrections without the contributions of G 0 terms to partition function ratios.…”
Section: Equilibrium Constant K With Corrections Beyond Harmonic Levelmentioning
confidence: 90%
See 1 more Smart Citation
“…For the water vapor internal equilibrium reaction: H 2 O + D 2 O = 2HDO, large deviations were found between theoretical studies and experiments (Pyper et al, 1967;Pyper and Newbury, 1970;Pyper and Christensen, 1975). Wolfsberg (1969) showed that it was not sufficiently accurate to add anharmonic corrections without the contributions of G 0 terms to partition function ratios.…”
Section: Equilibrium Constant K With Corrections Beyond Harmonic Levelmentioning
confidence: 90%
“…Table 5 The comparison of equilibrium constant K calculated from this study and those from Wolfsberg et al (1970), Bron et al (1973), Richet et al (1977) and experiments. Wolfsberg et al (1970) and Bron et al (1973) Richet et al (1977 This study Experiments Friedman and Shiner(1966); (b) Pyper and Christensen (1975); (c) Pyper and Newbury (1970); (d) Richet et al (1977); (e) Bron et al (1973).…”
Section: Equilibrium Constant K With Corrections Beyond Harmonic Levelmentioning
confidence: 92%
“…This shows that a 1% error in the molar fraction leads to an error of about 5% in the equilibrium constant when m 10 and m 30 are near 1:1. (13)) but they refer to reactions in the liquid phase. (14) which is 3.95 Ϯ 0.12.…”
Section: Equilibrium In Water Mixturesmentioning
confidence: 99%
“…The equilibrium constant for this reaction has been measured many times for the gaseous phase (see, for example, (13,14)) but data for solutions are scarce. Gold and Tomlinson (14) measured the equilibrium constant by using 1 H NMR spectra similar to those given in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, Pyper et al [6] measured the equilibrium constants of Hydrogen-H 2 O isotopic exchange reaction; Benedict et al [7] measured the microwave spectrum and rotational constants for the ground state of D 2 O.…”
Section: But the Reactive Channel O + Dd→d 2 O Has A Saddle Point Thmentioning
confidence: 99%